Electromagnetic fields and waves : microwave and mmWave engineering with generalized macroscopic electrodynamics /: microwave and mmWave engineering with generalized macroscopic electrodynamics. ([2019]) - Nefyodov, Eugene I; Smolskiy, Sergey M
No abstract available